The role of floating mucilage in the invasive spread of the benthic microalga Chrysophaeum taylorii. (1st June 2016) - Caronni, Sarah; Delaria, Maria Anna; Heimann, Kirsten; Macri, Giovanni; Navone, Augusto; Panzalis, Pieraugusto; Ceccherelli, Giulia
Abstract: Chrysophaeum taylorii Lewis & Bryan (Pelagophyceae) is a mucilage‐producing benthic microalga that has recently begun to spread in the Mediterranean Sea, where a range expansion is occurring. This paper presents the results of three field experiments that aimed to increase the knowledge on mucilage provision mechanisms for this benthic microalga and to evaluate the importance of mucilage in its range expansion. By means of two correlative field experiments (several years of data were considered to encompass the variability of mucilage cover) we found that, on the sea bottom, mucilage cover does not depend on epilithic cell density and that both its cover and settling are affected by water flow. We also tested the hypothesis that cells embedded in floating mucilage fall on the underlying substratum, where their abundance depends on water flow. To this aim, in the field we manipulated the presence of floating mucilaginous aggregates in cages with different levels of exposure to winds. The abundance of C. taylorii cells on the substratum under cages with mucilage was compared with that of two control treatments: cages without mucilage and mucilage in still water, in the field and lab, respectively. The results suggested that mucilage can represent an excellent strategy for the species to disperse, as C. taylorii cells fall from the floating mucilage and, if the water flow is unimportant, settle on hard substrata just underneath the cage. This study enriches the portfolio of knowledge of the dispersal strategies of microalgae and contributes to the understanding of the spread of invasive species.